Isolation of Salmonella from meat, blood, faeces, bile and Iymphnodes of different species of animals - PATURKAR, A M; SHERIKAR, A T; MURUGKAR, H V (The Indian Journal of Animal Sciences, 2013)
Samples (168) comprising 7 samples each of blood, faeces. lymphnode and bile, and 14 samples of meat from cattle, buffaloes. pigs and goats. were analysed for Salmonella. The 10 (5.9%) Salmonella- positive samples contained serotypos .’S liverpool. S. saintpaul and S. adelaide. Six isolates were obtained from pigs. 2 each from the faeces (both S. liverpool) and lymphnodos (S.liverpool and S. saintpaul) and 1 each from bite (S. adelaide) and meat (S. saintpaul). Two meat samples each of buffaloes and goats also showed S. saintpaul. No Salmonella were isolated from cattle.